Day of Tribulation: Japanese VR Horror Game - Odysseos, Panagiota (My University, 2023)
This thesis researches the game design elements used in psychological horror games and how they can be implemented in a Virtual Reality environment. The goal is to develop an immersive Japanese horror VR game experience, that focuses on game design elements of psychological horror, and the use of puzzle mechanic system for story progression. The plot of the game, named “Day of Tribulation”, is heavily inspired and influenced by Japanese mythology and folklore, giving emphasis on the style of gameplay of Asian Horror. Accompanied, with the use of auditory hallucinations and environmental storytelling, the player will have to figure out the truth behind the curse mark and its origins. This thesis went through various phases of implementation. Firstly, an extensive literature review was done on the game and level design process of developing VR games, the game design elements of psychological horror games and the use of auditory hallucinations and environmental storytelling to create an effective horror game atmosphere. The pre-production phase focused on the research of game assets to be able to aid the next phase of design, that includes the process of creating the worldbuilding and the story. Following, the production phase took place, which was the design of the game’s playthrough and levels, the creation of some assets and the development of the game. Finally, a user testing was done that concluded with successfully implementing the psychological horror elements and creating the horror atmosphere in the VR game.
Keywords: VR Experience; Psychological Horror; Japanese Mythology; Environmental Storytelling; VR Horror Game